Individual thrombin generation and spontaneous bleeding rate during personalized prophylaxis with Nuwiq® (human‐cl rhFVIII) in previously treated patients with severe haemophilia A. Issue 4 (31st May 2018) - Dargaud, Y.; Negrier, C.; Rusen, L.; Windyga, J.; Georgiev, P.; Bichler, J.; Solomon, C.; Knaub, S.; Lissitchkov, T.; Klamroth, R.
Abstract : Introduction: For individuals with haemophilia A, prophylaxis with factor VIII (FVIII) is typically directed towards trough activity >1 IU/dL; however, some patients still experience spontaneous bleeding events (sBEs). Aim: Aims were to evaluate relationships of endogenous thrombin potential (ETP) and FVIII:C with occurrence of clinical bleeding. Methods: GENA‐21 was a prospective, open‐label, phase IIIb study investigating the safety and efficacy of Nuwiq ® (human‐cl rhFVIII) in previously treated adults with severe haemophilia A. The study included a 72‐hour pharmacokinetic (PK) evaluation phase and a 6‐month personalized prophylaxis phase in which treatment was guided by PK parameters. This subanalysis assessed FVIII:C by one‐stage assay and ETP by thrombin generation assay in blood samples. Results: Baseline mean ETP was lower in the 7 patients who experienced sBEs during personalized prophylaxis versus 25 who did not (n = 32 with data from PK phase and prophylaxis phase; P = .0002). During personalized prophylaxis (n = 49), only patients with lower median trough ETP experienced sBEs (8/49 patients; ROC AUC = 0.9421; P < .0001); there was no significant relationship for FVIII:C in predicting sBEs (ROC AUC = 0.5838; P = .4750). Directly following infusion of human‐cl rhFVIII, ETP was lower in patients who experienced sBEs versus those who did not ( P = .0002), whereas FVIII:C did not differ significantly between these groups. Conclusions: In adults with severe haemophilia A and reduced thrombin generation, increased frequency of spontaneous bleeding was observed irrespective of trough FVIII levels. Thus, personalized prophylaxis should take into account variables other than FVIII:C. Large prospective trials are needed to verify ETP as a marker for spontaneous bleeding.